Ovarian Granulosa Cell Tumor with Estrogen-Induced Cystic Endometrial Hyperplasia in a Female Dog - Yadav, Vinay; Bisla, Amarjeet; Singh, Reetinder; Sood, Rajat (The Indian Journal of Animal Reproduction, 2026)
Granulosa cell tumors (GCTs) are uncommon ovarian neoplasms in dogs and are frequently associated with prolonged estrus and uterine pathology due to their hormonal activity. A seven-year-old German Shepherd bitch was presented to TVCC, GADVASU, Ludhiana, with a history of purulent vaginal discharge of more than forty days’ duration, irreg ular estrous cycles, polydipsia, polyuria, lethargy, and intermittent vomiting. Ultrasonographic examination revealed a non-homogeneous hypoechoic mass measuring 3.5 cm in diameter at the left ovarian site, along with features suggestive of cystic endometrial hyperplasia. Ovariohysterectomy was performed under general anesthesia. Gross and histopatho logical examination confirmed a Sertoli-like pattern granulosa cell tumor with concurrent cystic endometrial hyper plasia and endometritis. The postoperative recovery was uneventful, highlighting ovariohysterectomy as an effective treatment for canine granulosa cell tumors.
Keywords: Bitch; Cystic endometrial hyperplasia; Granulosa cell tumors; Ovariohysterectomy